EFSUMB Guidelines and Recommendations on the Clinical Use of Liver Ultrasound Elastography, Update 2017 (Long Version) - Dietrich, Christoph F.; Bamber, Jeffrey; Berzigotti, Annalisa; Bota, Simona; Cantisani, Vito; Castera, Laurent; Cosgrove, David; Ferraioli, Giovanna; Friedrich-Rust, Mireen; Gilja, Odd Helge; Goertz, Ruediger Stephan; Karlas, Thomas; de Knegt, Robert; de Ledinghen, Victor; Piscaglia, Fabio; Procopet, Bogdan; Saftoiu, Adrian; Sidhu, Paul S.; Sporea, Ioan; Thiele, Maja (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
We present here the first update of the 2013 EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) Guidelines and Recommendations on the clinical use of elastography, focused on the assessment of diffuse liver disease. The first part (long version) of these Guidelines and Recommendations deals with the basic principles of elastography and provides an update of how the technology has changed. The practical advantages and disadvantages associated with each of the techniques are described, and guidance is provided regarding optimization of scanning technique, image display, image interpretation, reporting of data and some of the known image artefacts. The second part provides clinical information about the practical use of elastography equipment and the interpretation of results in the assessment of diffuse liver disease and analyzes the main findings based on published studies, stressing the evidence from meta-analyses. The role of elastography in different etiologies of liver disease and in several clinical scenarios is also discussed. All of the recommendations are judged with regard to their evidence-based strength according to the Oxford Centre for Evidence-Based Medicine Levels of Evidence. This updated document is intended to act as a reference and to provide a practical guide for both beginners and advanced clinical users.
Keywords: guidelines; liver; fibrosis; chronic liver disease; hepatitis; chronic viral hepatitis; shear wave elastography; strain elastography; alcoholic hepatitis; NAFLD